EFFECTS OF BIRTH WEIGHT AND POSTNATAL HIGH-FAT DIET ON GROWTH PERFORMANCE, CARCASS AND MEAT QUALITY IN PIGS - J. B. Liu; J. He (Journal of Animal and Plant Sciences, 2014)
The current study was conducted to investigate the effects of birth weight and postnatal high-fat (HF) diet fed to pigs on growth performance, carcass composition, and meat quality traits. Twenty normal birth weight (NBW) and twenty intrauterine growth retarded (IUGR) barrows were fed a control diet or a HF diet from weaning to slaughter. IUGR pigs had a lower average daily gain and feed intake than NBW pigs. At slaughter, dressing yield decreased, whereas longissimus muscle (LM) area and back fat thickness increased in IUGR pigs compared with NBW pigs. The pH45min, lightness (L*), cooking loss, drip loss, and activity of glucose-6-phosphate dehydrogenase (G6-PDH) in LM were reduced in IUGR pigs than NBW pigs. Moreover, IUGR pigs exhibited greater intramuscular fat (IMF) content, yellowness (b*), Warner-Bratzler shear force, and activity levels of fatty acid synthase (FAS) compared to NBW pigs. The IMF and activity levels of G6-PDH were higher in LM of pigs fed a HF diet than pigs fed a control diet. In addition, HF feeding depressed FAS and malic enzyme activity. The interactions between birth weight and postnatal diet for LM area, back fat thickness, pH45min, and IMF in LM were observed in this study. In conclusion, our results suggested that IUGR pigs had a greater ability to deposit lipid in adipose tissue and skeletal muscle than NBW pigs when fed a HF diet, while producing less tender meat than NBW pigs.
Keywords: birth weight; high-fat diet; meat quality; pig